The Fetal Magnetic Resonance Imaging Experience in a Large Community Medical Center - Ghobrial,Peter M; Levy,Rebecca A; O’Connor,Stephen C
Fetal magnetic resonance imaging (MRI) continues to prove a useful problem solving tool for diagnostic and management decision making issues encountered in the antenatal period. In this paper, we attempt to review basic fetal MRI protocol considerations and demonstrate key imaging findings through multiple modalities, with pathologic correlation in several cases. A study of five fetal MRI cases, from our institution, were selected in order to highlight both the indications for, and benefits obtained from this advanced imaging technique. Fetal MRI proved useful in each case in better defining fetal anomalies, especially where ultrasound (due to drawbacks such as shadowing by pelvic bones) was unable to be completely diagnostic. The more in-depth study made possible by MRI also helped with formulation of disease prognosis and estimation of survival chances of the fetus. Further, MRI as a diagnostic and prognostic tool has become more ubiquitous across the medical community. This imparts tangible benefit to patients, who are now able to find this service within arm's reach. Whereas previously these patients were obligatorily referred up to 90 miles away from our centre for further medical work-up, now a large percentage can obtain their prenatal imaging and perinatal care locally. In addition, medical education benefits as new types of cases, those with pathology of the antenatal period, are retained for work-up and management in these large community settings. Cases from our institution exemplify these types of pathologies, from fetal chest masses to a syndromic presentation of bilateral renal agenesis.